FEASIBILITY STUDY OF PURIFIED BIOGAS INTO GAS BOTTLING IN INDONESIA - Qoriatul Fitriyah; Muhammad Prihadi Eko Wahyudi (Politeknik Negeri Batam, 2020)
In 2007, Indonesian government applied a program called as “Zero Kero” as an effort to save the government budget in terms of providing subsidies and as a step to diversify energy supplies to reduce the country's dependence on petroleum. It basically convert the fuel used for household cooking from kerosene to liquefied petroleum gas (LPG) sourced from natural gas. In the other hand, Indonesia produces 66-67 million waste in 2019 with organic waste reached 60%.Most of this waste is thrown away in landfill and left abandoned. Meanwhile, organic waste can actually be reprocessed, one of them as a main source of biogas plant. The gas then will be filtered, compressed and liquefied as a replacement of LPG. This paper will conduct a feasibility study of biogas bottling from organic waste in Indonesia.